Pengaruh Foot Massage terhadap Tekanan Darah dan Nadi di Ruang Intensive Care Unit (ICU): Literature Review - Achmad Jaya Saputra; Slamet Purnomo (Universitas Duta Bangsa Surakarta, 2021)
Introduction: The common occurrence patients in the Intensive Care Unit (ICU) is an unstable blood pressure andpulse. Blood pressure and pulse increase in ICU patients due to increased vasomotor activity in the medulla andcauses vasoconstriction of arterioles. Therefore, it is necessary to estimate the selection of interventions that havean influence on blood circulation, a good intervention given by nurses is foot massage.Objectives: This study was to conduct a systematic review of foot massage on blood pressure and pulse in ICUpatients.Methods: This study uses a Literature Review, with a systematic literature study in analyzing existing data with asearch method that involves a critical review process in selecting studies.Results: The data used by 10 national and international articles were obtained from the results of screening anumber of articles from Goggle Scholar, Search gate and PubMed. Based on the results of the journals collected,there is a significant effect of foot massages on blood pressure and pulse in ICU patients.Conclusions: Based on a literature review study, there is a significant effect of foot massage therapy on bloodpressure and pulse of patients in the ICU.